THEORETICAL AND METHODOLOGICAL BASIS OF HOLISTIC APPROACH TO ORGANIZATION - Olga Aleksandrovna Boris (Вестник Северо-Кавказского федерального университета, 2022)
The article explored the basis for a holistic approach, a comparison of the «holism» definitions is shown and the study of each founder’s role of this methodology in its development are studied.